Static and dynamic properties of decane/water microemulsions stabilized by cetylpyridinium chloride cationic surfactant and octanol cosurfactant. Issue 59 (1st October 2020) - Lemaalem, M.; Ahfir, R.; Derouiche, A.; Filali, M.
Abstract : We report a molecular dynamics simulation using a proven effective interaction potential to study the physical properties of decane/water microemulsions. Abstract : Molecular dynamics simulation (MD) is used to study the static and dynamic properties of positively charged decane/water microemulsions, for various volume fractions Φ (2.8%, 6.98%, 14%, and 26.5%). An effective hybrid potential combining three potentials, namely the hard-sphere repulsive potential, the van der Waals attractive potential, and the Yukawa repulsive potential, is used to describe the microemulsion interactions. The microemulsion shape is determined using the renormalized spectra in Porod representation. The appropriate potential parameters are tested using the Ornstein–Zernike integral equation approach with the Hypernetted Chain (HNC) closure relation by a comparison between the structure factor calculated from HNC and that obtained from Small Angle Neutron Scattering experiments (SANS). Thus, the micro arrangements of microemulsions have been analyzed using the pair correlation function g ( r ) and the structure factor S ( q ) obtained from HNC, SANS, and MD simulation using these parameters. The microemulsion dynamic properties were discussed using the mean-square displacement (MSD) and the diffusion coefficient D c calculated from MD simulations.